The effectiveness of compassion-focused therapy on anxiety caused by romantic breakup: Single case - Mina Soltani; Maryam Fatehizadeh (فصلنامه علمی- پژوهشی اصول بهداشت روانی, 2022)
Introduction: The purpose of this study was to investigate the effect of Compassion-Focused Therapy (CFT) on anxiety caused by romantic breaking up in young girls. Materials and Methods: In this study conducted in 2021 in Isfahan, Iran, three female participants with the experience of breaking up a romantic relationship were selected by the convenient sampling method. They underwent individual compassion-focused therapy during eight 90-minute sessions. Participants fulfilled Beck Anxiety Inventory (BAI), Love Trauma Inventory (LTI) and the Minnesota Multidimensional Personality Questionnaire (MMPI 2-RF). The data were analyzed by baseline change index, visual mapping, and recovery percentage formula.